SARS-CoV-2 in Horses in the Thrace Region of Turkey - Uslu, Ali; Balevi, Asli; Sayin, Zafer; Adiay, Cumhur; Tekindal, Mustafa Agah; Erganis, Osman (Acta Scientiae Veterinariae, 2024)
Background: People spent more time at home as part of the precaution taken after the COVID-19 pandemic. In this stage, human beings began to own more pets and spend more time with them. One of the most significant questions during this period was whether COVID-19 could be transmitted to pets. Beta coronavirus was already known in the veterinary field to cause diseases with different pathogenicity in many animal species. Over time, research has shown that the disease can be transmitted to pets and wild animals. Many studies have shown that equines could be infected with this disease. This study serologically investigated whether COVID-19 was transmitted to horses from humans. Materials, Methods & Results: In this cohort study, 510 horse serums were collected from Çanakkale (n = 80), Istanbul (n = 200), Tekirdağ (n = 75), and Kırklareli (n = 155), provinces in the Thrace region of Turkey. The sampling was conducted in October and December 2021, when the SARS-CoV-2 pandemic. The samples were grouped as 0-1, 1-5, 6-10, and 11-15 ages. Enzyme-linked immunosorbent assay (ELISA) plates were coated with the whole inactive SARS-CoV-2 virus at five µg/ml. Hyperimmunized horse sera was used as a positive control, and newborn foal serums that did not drink colostrum were used as a negative control. Positive and negative control sera were also tested by virus neutralization assay (VNA). Primary and secondary serum dilution was determined using the checkerboard method. Accordingly, the test serum dilution was 1/12,800, and the secondary antibody dilution was 1/2,500. The classical indirect ELISA steps were followed. Horses, 192 (37.6%) were bred in riding clubs, and 318 (62.4%) were bred in individual barns. OD values ranged between 0.05-1.39. The cut-off value prepared by ROC analysis with 100% sensitivity, 99.78% specificity, and 95% confidence interval was defined as the OD 0.78 limit value in determining positivity. In this study, 60 (11.76%) horses tested serologically positive for SARS-CoV-2. The highest infection rates were in Istanbul (13%) and Kırklareli (13.3%), and the lowest were in Canakkale (8.75%). According to the chi-square test, there was no statistically significant difference in infection rates between cities (P > 0.05). It was determined that horses in the 6-10 age group and in riding schools had a statistically higher rate of contracting the disease than horses in other age groups and barn (P < 0.05). The infection rate was found to be very low in horses younger than 1-year-old and close to 15-year-old. Discussion: The infection was more intense in the 1-10 age group and riding clubs. The lower incidence of disease was seen in old and young horses because of their lack of use in equestrian activities. According to the results of this study, 11.76% of 510 horses were found to be SARS-CoV-2 positive. As a result of another study conducted on the presence of SARS-CoV-2 in 587 racehorses with a single or several fixed riders, it was reported that 5.9% was positive. In this respect, the results were found to be compatible. The SARS-CoV-2 seropositivity rate in cats and dogs has been reported as 4-43.8% and 3.4-23.5%, respectively. It was thought that the lower infection rate in horses as pets compared to dogs was related to the fact that horse riding was done outdoors, and COVID-19-positive individuals were prohibited from going out to do these activities in the acute period and rested at home during the shedding period. Compared to this study and other studies, it has been determined that the infection in horses is silent and has a short viremia period, and this related seropositivity can be detected. Sick humans should be more careful about zooanthropozoonosis diseases that can be transmitted from humans to horses. Keywords: Covid-19, cohort study, horse, SARS-CoV-2, seropositivity, zooanthropozoonosis.